Tell me everything : a novel [compact disc, unabridged] - Strout, Elizabeth (Amgash, 2024)
It's autumn in Maine, and the town lawyer Bob Burgess has become enmeshed in an unfolding murder investigation, defending a lonely, isolated man accused of killing his mother. He has also fallen into a deep and abiding friendship with the acclaimed writer, Lucy Barton, who lives down the road in a house by the sea with her ex-husband, William. Together, Lucy and Bob go on walks and talk about their lives, their fears and regrets, and what might have been. Lucy, meanwhile, is finally introduced to the iconic Olive Kitteridge, now living in a retirement community on the edge of town. Together, they spend afternoons in Olive's apartment, telling each other stories. Stories about people they have known, "unrecorded lives," Olive calls them, reanimating them, and, in the process, imbuing their lives with meaning.